2019
DOI: 10.3389/fphys.2019.01267
|View full text |Cite
|
Sign up to set email alerts
|

Bitter Taste Receptors (TAS2Rs) in Human Lung Macrophages: Receptor Expression and Inhibitory Effects of TAS2R Agonists

Abstract: BackgroundBitter-taste receptors (TAS2Rs) are involved in airway relaxation but are also expressed in human blood leukocytes. We studied TAS2R expression and the effects of TAS2R agonists on the lipopolysaccharide (LPS)-induced cytokine release in human lung macrophages (LMs).MethodsLung macrophages were isolated from patients undergoing surgery for carcinoma. We used RT-qPCR to measure transcripts of 16 TAS2Rs (TAS2Rs 3/4/5/7/8/9/10/14/19/20/31/38/39/43/45 and 46) in unstimulated and LPS-stimulated (10 ng.mL–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 63 publications
(107 reference statements)
3
67
0
Order By: Relevance
“…Indeed, we found that TAS2R10 may help prevent a cytokine storm because it can regulate natural killer cell‐mediated cytotoxicity, chemokine signaling pathways, T cell receptor signaling pathways, TNF signaling pathways, and others (Figure 3). A recent report confirmed our results that TAS2R members 3, 4, 5, 9, 10, 14, 30, 39, and 40 were involved in the inhibition of cytokine production, such as TNF‐α, CCL3, and CXCL8, in human lung macrophages 49 . It reported that quinine, denatonium, dapsone, colchicine, strychnine, chloroquine, erythromycin phenanthroline, ofloxacin, and carisoprodol worked in this inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, we found that TAS2R10 may help prevent a cytokine storm because it can regulate natural killer cell‐mediated cytotoxicity, chemokine signaling pathways, T cell receptor signaling pathways, TNF signaling pathways, and others (Figure 3). A recent report confirmed our results that TAS2R members 3, 4, 5, 9, 10, 14, 30, 39, and 40 were involved in the inhibition of cytokine production, such as TNF‐α, CCL3, and CXCL8, in human lung macrophages 49 . It reported that quinine, denatonium, dapsone, colchicine, strychnine, chloroquine, erythromycin phenanthroline, ofloxacin, and carisoprodol worked in this inhibition.…”
Section: Discussionsupporting
confidence: 87%
“…More importantly, TAS2Rs mediated significant inhibition of the release of histamine and PGD2 from IgE-receptor-activated primary human mast cells, which suggests that TAS2R receptors may mediate anti-inflammatory responses. TAS2R expression and the effects of TAS2R agonists on lipopolysaccharide (LPS)-induced cytokine release in human lung macrophages (LMs) were studied by Grassin-Delyle et al [ 36 ]. They found that 16 TAS2Rs are expressed in human LMs with the most abundant transcripts being of TAS2R8 , 14 , 19 , 39 and 46 .…”
Section: Tas2r Receptors In Lower Airwaysmentioning
confidence: 99%
“…CQ is a broad-spectrum agonist of bitter taste receptors (TAS2R), a family of G-protein receptors expressed in lungs (airway smooth muscle, airway epithelial cells, lung macrophages, mast cells) and leukocytes, notably lymphocytes, innate lymphoid cells, and monocytes. TAS2R stimulation induces defense mechanisms such as an increase in NO (nitric oxide) production, stimulating mucociliary clearance and exerting antibacterial, anti-inflammatory and muscle relaxant effects ( 53 55 ).…”
Section: General Mechanisms Of Cq/hcq Actionsmentioning
confidence: 99%
“…Deacidification of intracellular organelles is not the only immunomodulatory mechanism of CQ. Extragustatory TAS2R stimulation exerts anti-inflammatory properties and bronchodilator activities, and CQ is a TAS2R agonist ( 53 55 ). TAS2R stimulation in lung macrophages exposed to CQ significantly inhibited LPS-mediated production of TNFα, CCL3 (C-C motif chemokine ligand 3) and CXCL8 (C-X-C motif chemokine ligand 8), but also of the regulatory cytokine IL-10, suggesting that, at least in this macrophage population, inhibition of the proinflammatory cytokines was not related to IL-10 overexpression ( 55 ).…”
Section: Mechanisms Of Cq/hcq-induced Immune Modulationmentioning
confidence: 99%